Новые раскопки курганов в могильнике Скоробор - Шрамко, Б А. (Давнина. Харківський історико-археологічний щорічник, 2016)
Summary Shramko B. A. New Excavations of the Barrows in the Skorobor Burial Ground Skorobor cemetery was studied in 1965,1972,1975 and 1979 by die expedition of Kharkov State University. The excavations studied 25 barrows. The graves of the 7th – 4th centuries B.C. were founded in the cemetery. The excavations have shown direct connection of the ceinetry with the nearby hill fort of Skythian period at Belsk Poltava Region.